2015
DOI: 10.1159/000381915
|View full text |Cite
|
Sign up to set email alerts
|

Processing Body Formation Limits Proinflammatory Cytokine Synthesis in Endotoxin-Tolerant Monocytes and Murine Septic Macrophages

Abstract: An anti-inflammatory phenotype with pronounced immunosuppression develops during sepsis, during which time neutrophils and monocytes/macrophages limit their Toll-like receptor 4 responses to bacterial lipopolysaccharide (LPS/endotoxin). We previously reported that during this endotoxin-tolerant state, distinct signaling pathways differentially repress transcription and translation of proinflammatory cytokines such as TNFα and IL-6. Sustained endotoxin tolerance contributes to sepsis mortality. While transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 46 publications
(103 reference statements)
0
9
0
Order By: Relevance
“…Recent studies indicate that proinflammatory stimulation, including LPS/ TLR4 engagement, is associated with reprogramming of monocytes that results in diminished responses to second challenge with LPS, a condition known as endotoxin tolerance (46,47). AMPK activation has been shown to reduce proinflammatory cytokine production effectively in LPS-stimulated macrophages (38,48,49).…”
Section: Ampk Activation Prevents Macrophage Reprogramming Into An Enmentioning
confidence: 99%
“…Recent studies indicate that proinflammatory stimulation, including LPS/ TLR4 engagement, is associated with reprogramming of monocytes that results in diminished responses to second challenge with LPS, a condition known as endotoxin tolerance (46,47). AMPK activation has been shown to reduce proinflammatory cytokine production effectively in LPS-stimulated macrophages (38,48,49).…”
Section: Ampk Activation Prevents Macrophage Reprogramming Into An Enmentioning
confidence: 99%
“…Increased cytokine secretion may be responsible for the inflammatory process, including neutrophil migration [ 21 ], and macrophages are a significant source of cytokines [ 22 ]. To further explore the anti-inflammatory action and mechanisms of FTA, we researched the effect on the cytokines expressions in zymosan-stimulated macrophages.…”
Section: Resultsmentioning
confidence: 99%
“…44 Moreover, in vitro experiments revealed that formation of p-bodies is critical to suppress inflammatory cytokine expression in endotoxin tolerant macrophages. 45 When we genetically removed p-bodies in hCT-MSCs by deleting DDX6 via Crispr/Cas9, DDX6-KO hCT-MSCs failed to reprogram monocytes and macrophages and suppress T H cells in vitro ( Figure 5D-G). in vivo data using an LPS-induced lung inflammation model demonstrated that DDX-KO hCT-MSC lost their ability to suppress inflammation and decrease the surface expression of MHC class II on infiltrating monocytes and macrophages that engulfed MSCs ( Figure 6C).…”
Section: Although Efferocytosis Likely Contributes To Engulfing and Cmentioning
confidence: 99%